(untitled) (Journal of Mathematics Mechanics and Computer Science, 2024)
The paper presents a model of information system designed to evaluate tourism objects based on information from web resources and social networks. When describing the model, the main entities such as data object, user, option, comment, tourism object, tourism organization and tone definition term were identified and described in detail. The relationships between the above entities of the information system are also defined. The core of the model is a data object, which stores complete information about the resource and is described to a greater extent through metadata. The main stages of model realization are given, which includes four steps: creation of tourism object database, collection and processing of comments, creation of tone definition dictionary and stage of tourism object evaluation. The paper also touches upon the issues related to the definition of the needs of tourists and tourism organizations.